1999
DOI: 10.1016/s0168-6445(99)00007-8
|View full text |Cite
|
Sign up to set email alerts
|

Ribozymes: the characteristics and properties of catalytic RNAs

Abstract: Ribozymes, or catalytic RNAs, were discovered a little more than 15 years ago. They are found in the organelles of plants and lower eukaryotes, in amphibians, in prokaryotes, in bacteriophages, and in viroids and satellite viruses that infect plants. An example is also known of a ribozyme in hepatitis delta virus, a serious human pathogen. Additional ribozymes are bound to be found in the future, and it is tempting to regard the RNA component(s) of various ribonucleoprotein complexes as the catalytic engine, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 89 publications
(141 reference statements)
1
34
0
3
Order By: Relevance
“…The presence of a poly(A) tail is generally thought to be a critical determinant of mRNA stability+ For some mRNAs, poly(A) shortening or removal is the ratedetermining event in their decay, whereas, for others, it may be an obligate event in their degradation, but it is not the rate-determining step (Chen et al+, 1995;Caponigro & Parker, 1996;+ The presence of a poly(A) tail provides an mRNA with a binding site for poly(A)-binding protein, which, in turn, serves to promote translational initiation and antagonize mRNA decapping in the cytoplasm (Gallie et al+, 1989;Caponigro & Parker, 1995;Tarun & Sachs, 1996)+ In this study, the TRP4-ribozyme allele produces a transcript lacking a poly(A) tail and, as a consequence, it would be predicted that this mRNA would be susceptible to nucleolytic attack and considerably less abundant than its wild-type counterpart+ In contrast, we found that the nonpolyadenylated ribozyme transcript accumulated to levels indicative of little, if any, change in stability+ Maintenance of the stability of the poly(A)-deficient TRP4-ribozyme mRNA is likely to be a result of the action of the ribozyme in generation of the mRNA 39 end, and not to some internal TRP4 sequence features, as deletion of the TRP4 39 UTR resulted in a significant decrease in the amount of TRP4 mRNA+ In support of this idea, a previous study determined that the presence of a ribozyme in an mRNA is not sufficient to render it more labile (Donahue & Fedor, 1997)+ Several plausible explanations could account for the unchanged stability of TRP4-ribozyme mRNA+ The secondary structure formed by the hammerhead ribozyme, or the terminal 29-39cyclic phosphate (Tanner, 1999), instead of a 39-OH, might impede the accessibility of 39 exonucleases to the mRNA+ Alternatively, the absence of a poly(A) tail might uncouple an otherwise linked mechanism in which decapping is triggered by deadenylation (Muhlrad et al+, 1994)+ A more likely explanation is that degradation of the TRP4 mRNA is normally associated with its translation (Jacobson & Peltz, 1996)+ In a manner previously exemplified by the MATa1 mRNA (Parker & Jacobson, 1990), impaired translation of the TRP4-ribozyme mRNA (see below) may reduce the extent to which ribosome-associated factors act to promote decay+…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The presence of a poly(A) tail is generally thought to be a critical determinant of mRNA stability+ For some mRNAs, poly(A) shortening or removal is the ratedetermining event in their decay, whereas, for others, it may be an obligate event in their degradation, but it is not the rate-determining step (Chen et al+, 1995;Caponigro & Parker, 1996;+ The presence of a poly(A) tail provides an mRNA with a binding site for poly(A)-binding protein, which, in turn, serves to promote translational initiation and antagonize mRNA decapping in the cytoplasm (Gallie et al+, 1989;Caponigro & Parker, 1995;Tarun & Sachs, 1996)+ In this study, the TRP4-ribozyme allele produces a transcript lacking a poly(A) tail and, as a consequence, it would be predicted that this mRNA would be susceptible to nucleolytic attack and considerably less abundant than its wild-type counterpart+ In contrast, we found that the nonpolyadenylated ribozyme transcript accumulated to levels indicative of little, if any, change in stability+ Maintenance of the stability of the poly(A)-deficient TRP4-ribozyme mRNA is likely to be a result of the action of the ribozyme in generation of the mRNA 39 end, and not to some internal TRP4 sequence features, as deletion of the TRP4 39 UTR resulted in a significant decrease in the amount of TRP4 mRNA+ In support of this idea, a previous study determined that the presence of a ribozyme in an mRNA is not sufficient to render it more labile (Donahue & Fedor, 1997)+ Several plausible explanations could account for the unchanged stability of TRP4-ribozyme mRNA+ The secondary structure formed by the hammerhead ribozyme, or the terminal 29-39cyclic phosphate (Tanner, 1999), instead of a 39-OH, might impede the accessibility of 39 exonucleases to the mRNA+ Alternatively, the absence of a poly(A) tail might uncouple an otherwise linked mechanism in which decapping is triggered by deadenylation (Muhlrad et al+, 1994)+ A more likely explanation is that degradation of the TRP4 mRNA is normally associated with its translation (Jacobson & Peltz, 1996)+ In a manner previously exemplified by the MATa1 mRNA (Parker & Jacobson, 1990), impaired translation of the TRP4-ribozyme mRNA (see below) may reduce the extent to which ribosome-associated factors act to promote decay+…”
Section: Discussionmentioning
confidence: 94%
“…termini generated by hammerhead cleavage to serve as substrates for poly(A) polymerase (Tanner, 1999;Zhao et al+, 1999)+ In yeast, it has been possible to obtain polyadenylation of a ribozyme-containing transcript (Egli & Braus, 1994), an event that most likely depends on RNA sequence context, that is, triggering cryptic cleavage/polyadenylation signals+ Because we were unable to detect any polyadenylated transcripts in RACE experiments we conclude that the TRP4-ribozyme mRNA does not contain any cryptic signals+ Although mRNA 39-end processing and nuclear export have been shown to be linked (Eckner et al+, 1991;Hilleren et al+, 2001), the TRP4-ribozyme mRNA appears to be efficiently exported from the nucleus+ It is unclear whether this occurs by pathways previously shown to be effective for nonpolyadenylated RNAs like rRNA and tRNAs (Moy & Silver, 1999;Sarkar et al+, 1999;Simos & Hurt, 1999) or by some other mechanism+ Unlike metazoans and their unadenylated histone mRNAs, there are no known examples of yeast RNA polymerase II transcripts that lack poly(A) tails (Goffeau et al+, 1996)+ Future studies to assess the mechanism by which such nonpolyadenylated mRNAs are exported will be of interest+…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples are the activities of siRNA and microRNAs (Zhang et al, 2002;Doi et al, 2003;Zeng et Goodman, 2004; Yekta et al, 2004;Kim et al, 2005b;Behlke, 2006;Ronemus et al, 2006;Valencia-Sanchez et al, 2006). Nevertheless, other reports have described reactions of direct RNA-mediated cleavage of RNA (Tanner, 1999;Lilley, 1999;Doudna & Cech, 2002;Sago et al, 2004). These reactions include self-cleaving of RNA [for example:…”
Section: Discussionmentioning
confidence: 99%
“…1 Their functional diversity can be attributed to the complex three-dimensional folds that RNA can assume via a multitude of secondary structures and tertiary interactions. 2,3 Ribozymes, therefore, provide a unique opportunity to correlate RNA structure and function.…”
Section: Introductionmentioning
confidence: 99%